Classical Rhetoric for the Modern Student - Corbett, Edward P.J. (New York Oxford University Press, 1965)
This book endeavors to present a coherent, realistic art of composition an adaptation of classical rhetoric. The men whom we inherited the classical system Aristotel, Cicero, and Quintilian firly believed thet some of the skills involved in process of composition could be taught. Having studied the practice of successful speaker and writers, they brought together a set of precepts to aid their students in acquiring those skills.
Keywords: Literature